Reducing Vancomycin Dosage in Children on ECMO with Renal Impairment - Bobrowski, Alexej; Höhn, René; Kubicki, Rouven; Fleck, Thilo; Zürn, Christoph; Maier, Sven; Kari, Fabian Alexander; Kroll, Johannes; Stiller, Brigitte (The Thoracic and Cardiovascular Surgeon, 2024)
Background Extracorporeal membrane oxygenation (ECMO) can influence pharmacokinetics. We investigated the vancomycin dosage in children on ECMO compared to critically ill children to determine the necessary dosage adjustment on ECMO.Methods Eight-year, single-center, retrospective cohort study at a tertiary heart center's pediatric cardiac intensive care unit (ICU) of children undergoing ECMO support. Our control group (non-ECMO) was critically ill children with delayed sternal closure after cardiac surgery. We included consecutively all children undergoing vancomycin administration. The starting dose was 10 to 15 mg/kg BW per dose, every 8 to 12 hours depending on age. The vancomycin trough level was maintained in the 10 to 20 μg/ml range.Results 85 total courses on ECMO and 99 non-ECMO courses were included. The ECMO group's daily vancomycin dose was significantly lower than non-ECMO's at a median of 33.3 and 38.5 mg/kg/d, respectively (p < 0.001). Vancomycin serum trough levels were similar between groups and within the target range. The ECMO group's daily vancomycin dose dropped faster over time, with a dose on day 3 of 28.7 and 33.7 mg/kg/d, respectively. The impact of renal function on vancomycin dosing was more apparent in the ECMO group. If the renal function was reduced at the start of treatment, the vancomycin dose was lower in the ECMO group compared to the non-ECMO group with renal impairment (22.5 vs. 42.1 mg/kg/d; p < 0.001). When renal function was normal, the doses were similar between groups.Conclusion In children on ECMO with impaired renal function at treatment initiation, lower vancomycin doses were necessary. Early therapeutic drug monitoring, even before reaching a steady state, should be considered.
Keywords: extracorporeal membrane oxygenation; ECMO; pediatric; kidney; pharmacokinetics; intensive care